Yield of Jatropha curcas L. inoculated with mycorrhiza and fertilized with sugarcane compost - Díaz-Hernández Brenda Gabriela; Aguirre-Medina, Juan Francisco; Díaz-Fuentes Víctor Hugo (Revista Mexicana de Ciencias Agrícolas, 2018)
With the aim of identifying the influence of Glomus intraradices and of sugarcane compost on the yield of Jatropha curcas L. under field conditions, we established the present experiment in a low fertility soil in Cotaxtla Veracruz during the winter of 2008. The "piñon" was propagated in a greenhouse with seeds collected in the state of Veracruz. They were transplanted to the field when they were 20 cm tall in a real frame system at a distance of 3 x 3 m. We developed four treatments distributed in random blocks with four replicates witness; control, 40 g of Glomus intraradices per plant, 1 kg of sugarcane compost, and 40 g of Glomus intraradices + 1 kg of sugarcane compost in randomized block design with four replicates. The treatments were applied when the plants were transplanted to the field. The experimental unit comprised ten plants. Stem thickness was evaluated, as well as other physiological variables of yield, at 6, 12, 20 and 26 months, which correspond to 180, 365, 680 and 780 days after sowing (DAS). The results indicate statistically significant differences in all variables for mycorrhizal treatments with and without the addition of sugarcane compost. It is concluded that the inoculation of Jatropha curcas L. with Glomus intraradices promotes the production of a greater number of fruits and seed weight. The combination of the mycorrhizal fungus and the sugarcane compost is a basis for increasing the yield of Jatropha.